A VAR Model for Monetary Policy Analysis in a Small Open Economy - Tor Jacobson; Per Jansson; Anders Vredin; Anders Warne (Sveriges Riksbank, 1999)
The interest in empirical studies of monetary policy has increased in the last decade. The deregulation of financial markets and the increased use of explicit policy rules and targets have made monetary policy more transparent and interesting for economic analysis. This paper demonstrates how a VAR model with long run restrictions justified by economic theory can be usefully applied in analyses of issues central to monetary policy: the effects of innovations in interest rates and other shocks; the short and long run relationships between prices and nominal and real exchange rates; the properties of an index of monetary conditions; dynamic forecasts of inflation; and the relation between inflation and the output gap
Keywords: C32; C52; C53; E31; E52; 330; Cointegration; Common stochastic trends; Monetary policy; Vector autoregressions